Preclinical Evaluation of Dimethyl Itaconate Against Hepatocellular Carcinoma via Activation of the e/iNOS-Mediated NF-κB–Dependent Apoptotic Pathway - Gautam, Anurag Kumar; Kumar, Pranesh; Raj, Ritu; Kumar, Dinesh; Bhattacharya, Bolay; Rajinikanth, P.S.; Chidambaram, Kumarappan; Mahata, Tarun; Maity, Biswanath; Saha, Sudipta (Frontiers in Pharmacology, 2022)
Hepatocellular carcinoma (HCC) affected a huge population globally, with the fifth and seventh highest mortality rates for men and women, respectively, as well as the third most prevalent cause of death among cancer patients. Dimethyl itaconate (DI) has been shown to be active against colorectal cancer via reducing the secretion of IL-1β at intestinal epithelial cells. In this study, DI was used as an anticancer in diethylnitrosamine (DEN) induced HCC in albino Wistar rats. In-vivo experiments were performed to characterize the function and molecular mechanism of action of DI against HCC via histopathology, enzyme linked immunosorbent assay (ELISA) and western blot analysis. 1H-NMR based metabolomics in the study of metabolic profiling. Molecular pathways insight, the DI has capacity to induce mitochondrial apoptosis through iNOS- and eNOS-induced activation of NF-κB/Bcl-2 family of proteins→CytC→Caspase 3 and 9 signaling cascade. NMR based serum mebtabolomic studies further demonstrated that perturbated metabolites in DEN induced HCC rats restored to normal after DI treatment. Finally, the all found data was suggested that the DI worked as anti-HCC. The anticancer property of DI was found to be comparable with the marketed chemotherapeutic agent, 5-fluorouracil.